NAFTA's and CUSFTA's Impact on International Trade - Romalis, John (The Review of Economics and Statistics, 2007)
This paper identifies NAFTA's effects on trade volumes and prices using detailed trade and tariff data. It identifies demand elasticities from the additional wedges driven between consumption patterns in NAFTA versus non-NAFTA countries caused by tariff reductions. Supply elasticities are identified using tariffs as instruments for observed quantities. Analysis of worldwide trade data for 5,000 commodities shows that NAFTA had a substantial impact on international trade volumes, but a modest effect on prices and welfare. NAFTA increased North American output and prices in many highly protected sectors by driving out imports from nonmember countries.